Captain Underpants and the perilous plot of Professor Poopypants : the fourth epic novel - Pilkey, Dav, 1966- (Pilkey, Dav, 1966- Adventures of Captain Underpants (Series), 2023)
When Professor Pippy P. Poopypants comes to Jerome Horwitz Elementary School to teach science, and he goes off the deep end because students make fun of his name, only Captain Underpants can save the school from the professor's perilous plot.